The importance of having an accurate multiphase flow correlations program - Ismail, Issham (Coastal & Offshore Engineering Institute, UTM, Malaysia., 1993)
In the petroleum industry, a suitable and an accurate vertical/directional multiphase flow correlation is normally required by the production engineer before completion and artificial lift design analysis can be performed with a reasonable degree of accuracy. Due to the repetitive step like nature of the calculations in a multiphase flow correlation, a simulation program is required to compute flowing pressure along the production string and wellbore. It is a wise move to check the accuracy of a simulation program at the first place because an inaccurate multiphase flow correlations program may cause severe error in facilities design.